Building options at project front-end strategizing : the power of capital design for evolvability - Biesek, Guilherme; Gil, Nuno (Project Management Institute, 2014)
Based on project risk management concepts, real options theory, and experimental results, this book proposes a framework that will improve the quality of outcomes and increase the project team¿́¿s accountability during the design phase. --